Le genre du posthumain : des transhumanismes à la théorie francophone - Mohamed Sami Alloun; Bachir Bouattou (Multilinguales)
Whether we speak of a « posthuman novel » (Amaury Dehoux) or of « posthumanist fiction » (Mara Magda Maftei), the proposed generic neologism once again compromises the already porous boundaries that distinguish the literary and scientific domains. Through this contribution, it is essentially a question of questioning the updating of science fiction by transhumanist authors.